1992
DOI: 10.1002/pi.4990290110
|View full text |Cite
|
Sign up to set email alerts
|

An explanation of the solubility behaviour of cellulose acetate in various solvents in terms of supermolecular structure formed by introduction of a substituent group into the glucopyranose unit

Abstract: An attempt is made to explain the solubility behaviour of cellulose derivatives with hydrophobic substituent groups towards several solvents in terms of supermolecular structure concepts, such as the degree of breakdown in intramolecular hydrogen bonds and conformational variety in the C l-O-Ck glucoside linkage, which depend on the total degree of substitution ( ( F ) ) and the distribution of substituent groups in the anhydroglucose (AHG) unit ((fk)) (k = 2, 3, and 6), and solvation.For this purpose, cellulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…SEM images given in Figure S2 show that the solvents alone are not responsible for these cell wall alterations. Previous studies have shown that isolated cellulose fibers or crystals can dissolve in organic solvents when they are highly substituted (through acetylation for instance), which could explain the observed cell wall alterations . However, the wood cell wall is a composite material where cellulose is not available in an isolated form; in our samples, cellulose fibers are embedded in the lignin–hemicelluloses matrix.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…SEM images given in Figure S2 show that the solvents alone are not responsible for these cell wall alterations. Previous studies have shown that isolated cellulose fibers or crystals can dissolve in organic solvents when they are highly substituted (through acetylation for instance), which could explain the observed cell wall alterations . However, the wood cell wall is a composite material where cellulose is not available in an isolated form; in our samples, cellulose fibers are embedded in the lignin–hemicelluloses matrix.…”
Section: Resultsmentioning
confidence: 71%
“…Previous studies have shown that isolated cellulose fibers or crystals can dissolve in organic solvents when they are highly substituted (through acetylation for instance), which could explain the observed cell wall alterations. 35 However, the wood cell wall is a composite material where cellulose is not available in an isolated form: in our samples, cellulose fibers are embedded in the ligninhemicelluloses matrix. Moreover, the calculated substitution degree for cellulose in our case is below the 0.5 critical value reported in literature (see calculations in Table S2).…”
Section: Characterization Of Thementioning
confidence: 94%
“…Guar is a relatively poor viscosifying agent, but increased viscosity or gels can be obtained by modiÐcation with galactose oxidase so that a crosslinking reaction takes place.99 Enzymic treatment of sugar beet pectin with a partially puriÐed Aspergillus niger enzyme preparation leads to a reduction of arabinose units, some deacetylation and demethoxylation, producing an improvement in the gelling properties, whereas acid treatment produces a di †erent polymer and gel properties.100 Similarly, di †er-ent pectin structures can be obtained from plants using di †erent protopectinases.101 Daicel Chemical Industries, in collaboration with the Osaka Municipal Technical Research Institute, have recently discovered microbes which modify cellulose acetate (CA) that will be utilized to develop new biodegradable plastics.102 These enzymic systems are presumably used to control the structure and properties of cellulose acetates, since Kamide and co-workers have devised an explanation of the solubility properties of CA based on supermolecular concepts such as degree of hydrogen bonding and conformation of the glycosidic links ; these properties are in turn dependent on the total degree of substitution and the distribution of glycosidic links. 103 Extensive work has been carried out on the acylation and deacylation of low molecular weight carbohydrates and some other hydroxyl-containing compounds in a wide range of non-conventional environments, which has lead to a reasonable understanding of the control of the selectivity of the reactions.104h108 Little of this technology appears to have been applied to polymers, although some examples are known. Deacetylation of xylan with acetyl esterase can modify solubility and render the material insoluble ;109 more complex xylan modiÐcations are achievable with the range of accessory enzymes available for the various substituents present in xylan.110 Deacetylation of chitin to various chitosans yielding products of wide-ranging applicability is well known.…”
Section: Structures Based On or Containing Saccharidesmentioning
confidence: 99%
“…Tashiro et al theoretically estimate that a particular sort of intramolecular hydrogen bond plays the most essential part in the elasticity of cellulose among all intra- and intermolecular hydrogen bonds; the elastic constant of cellulose decreases at the highest rate when the intramolecular hydrogen bond between O3−H3 and O5‘ in adjacent residues (symbols will be defined later) diminishes , In addition, Mattinen et al report that the flat rigid surface of crystalline cellulose makes a facile attachment possible for aromatic residues in cellulases, based on their NMR experiments . These results suggest that the ribbon structure of cellulose or cellooligosaccharides is intrinsic to their aggregation mechanism.…”
Section: Introductionmentioning
confidence: 99%